The occurrence and comprehensive control technology of pine wilt disease - Zhang, Wenhui (Pacific International Journal, 2024)
Pine wilt disease is known as one of the most harmful forestry diseases in the world. It is called the "cancer" of pine trees and seriously threatens forest resources and ecological environment. Therefore, it is of great significance to strengthen the prevention and control of pine wilt disease. This article introduces the pathogens and pathogenesis characteristics of pine wilt disease, summarizes the strategies adopted by Japan, the United States, South Korea and other countries to prevent and control pine wilt disease, and proposes specific comprehensive prevention and control technologies for pine wilt disease from the aspects of quarantine treatment, chemical control, biological control, and physical control. This study is expected to provide a reference for the sustainable development of forest resources and the effective prevention and control of pine wilt disease.